2013
DOI: 10.1093/eurheartj/eht159
|View full text |Cite
|
Sign up to set email alerts
|

Trends in age-specific coronary heart disease mortality in the European Union over three decades: 1980–2009

Abstract: AimsRecent decades have seen very large declines in coronary heart disease (CHD) mortality across most of Europe, partly due to declines in risk factors such as smoking. Cardiovascular diseases (predominantly CHD and stroke), remain, however, the main cause of death in most European countries, and many risk factors for CHD, particularly obesity, have been increasing substantially over the same period. It is hypothesized that observed reductions in CHD mortality have occurred largely within older age groups, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
185
0
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(221 citation statements)
references
References 18 publications
16
185
0
20
Order By: Relevance
“…1 Dyslipidemia is a major risk factor for cardiovascular events (CVEs). Lipid-lowering therapy, specifically statins, have become a cornerstone of treatment for dyslipidemia due to their marked lowering of low-density lipoprotein cholesterol (LDL).…”
mentioning
confidence: 99%
“…1 Dyslipidemia is a major risk factor for cardiovascular events (CVEs). Lipid-lowering therapy, specifically statins, have become a cornerstone of treatment for dyslipidemia due to their marked lowering of low-density lipoprotein cholesterol (LDL).…”
mentioning
confidence: 99%
“…During the first decade of our investigation (1983–2003), a statistically valid decrease in body mass index in Lithuanian men was observed (Nichols et al. 2013). Some authors associate the attenuation in declining mortality rate for obesity‐related disease (heart disease, stroke, and diabetes) with increased prevalence of obesity in today's society (Ma et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, evidence of an increasing diabetes prevalence trend in Lithuania among adults as well as of high rates of NCDs risk factors overall (Nichols et al. 2013). …”
Section: Discussionmentioning
confidence: 99%
“…2) Pseudopod epidemiology studies should be driven by specific well-defined hypotheses identified prior to and independent of the data analysis. [29,33,61,99]. 6) The study of proteomics, metabolomics, genomics, etc.…”
Section: The Independent Variables Are Not Accurate or Repeatablementioning
confidence: 99%